Back Cover: Enhanced Electrochemical Performance of Ti‐Doping Li1.15Ni0.47Sb0.38O2 as Lithium‐excess Cathode for Lithium‐ion Batteries (Chin. J. Chem. 12/2017). Issue 12 (4th December 2017) - Su, Xiaozhi; Wang, Xingbo; Chen, Haiping; Yu, Zhen; Qi, Jiaxin; Tao, Shi; Chu, Wangsheng; Song, Li
Abstract : The back cover picture shows X‐ray near edge absorption spectroscopy has been applied to cathode materials for lithium‐ion batteries to explore its structure‐activity relationship. The result shows that in the Li‐rich cathode Li1.15 Ni0.47 Sb0.38 O2, as a model system, Ti ions replaced the Li ions and then made an antistructure defect. It would change our understanding to the doped method for the cathode layer materials and benefit for designing other more powerful cathodes. In the picture, the road has been represented by the curve shape of the XANES of the as‐studied sample. The atomic arrangement around the Ti ion of the sample has been put into the tank position of the car. NSRL, National Synchrotron Radiation Laboratory, is the name of our laboratory. More details are discussed in the article by Chu et al. on page 1853–1860. Abstract : The back cover picture shows X‐ray near edge absorption spectroscopy has been applied to cathode materials for lithium‐ion batteries to explore its structure‐activity relationship. The result shows that in the Li‐rich cathode Li1.15 Ni0.47 Sb0.38 O2, as a model system, Ti ions replaced the Li ions and then made an antistructure defect. It would change our understanding to the doped method for the cathode layer materials and benefit for designing other more powerful cathodes. In the picture, the road has been represented by the curve shape of the XANES of the as‐studied sample. The atomic arrangement around the Ti ion of the sample has been put into the tank position of the car. NSRL, National Synchrotron Radiation Laboratory, is the name of our laboratory. More details are discussed in the article by Chu et al. on page 1853–1860.